(untitled) (Revista de Ensino em Artes, Moda e Design, 2024)
The teaching of typography needs more attention due to specific technical skills, such as drawing, software proficiency, methods, and font construction. This paper presents the Typographisms Project and analyzes the work of six students, selected for their style, readability, and legibility. The project adapted Falcão’s method (2021) to make the font construction process more accessible using graphic software and free platforms. Applied to 159 students from the Visual Communication course at IFSC -Campus Palhoça Bilingue in 2022 and 2023, the method can be improved and replicated in other design courses. The theoretical framework was based on learning by doing, active experimentation, and typography concepts. After the course, a survey showed that despite the complexity, education 4.0 promoted creativity and problemsolving skills.